Rekonstruksi Kewenangan Advokad alam Pengawasan Penyidikan: Analisis Yuridis Normatif Hak Keberatan (Right to object) terhadap Tindakan Penyidik dalam Konteks Asas Due Process Of Law KUHAP - Prayogi Aryovandri Podomi; Robby W. Amu; Nurmik K. Martam (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study was motivated by the increasing incidence of vehicle robbery crimes within the jurisdiction of the Gorontalo City Police, which have caused material losses, fear, and public anxiety in society. The purpose of this research is to analyze law enforcement efforts and crime prevention measures related to vehicle robbery, as well as to identify the criminological factors that encourage the occurrence of such crimes. The research employed a qualitative descriptive-analytical method, with data collected through interviews, documentation studies, and indirect observation. The results of the study indicate that the Gorontalo City Police have implemented repressive, preventive, and pre-emptive measures through investigations, inquiries, arrests of perpetrators, routine patrols, public order operations, utilization of CCTV, legal awareness campaigns, and cooperation with the community. The factors contributing to this crime include low self-control, weak family supervision, economic pressure, unemployment, peer influence, alcohol or narcotics abuse, and environmental conditions characterized by isolation and lack of supervision. This study suggests the need for increased patrols in vulnerable areas, installation of public security facilities, youth development programs, strengthening the role of families, and active community participation in maintaining public security and order.